Answer:
- 5
Step-by-step explanation:
Note that - (- 12) = + 12
Thus
- 17 - (- 12) = - 17 + 12 = - 5
It looks like Tom subtracted 12 from - 17, that is - 17 - 12 = - 29
4 * 45 = 180
265 - 180 = 85
85/5 = 17
They sold 17 rolls of patterned wrapping paper.
For this case we must simplify the following expression
![-5 + 7q + (- 5q) + (- 9q)](https://tex.z-dn.net/?f=-5%20%2B%207q%20%2B%20%28-%205q%29%20%2B%20%28-%209q%29)
We know that, by definition:
![+ * - = -](https://tex.z-dn.net/?f=%2B%20%2A%20-%20%3D%20-)
So, rewriting the expression we have:
![-5 + 7q-5q-9q =](https://tex.z-dn.net/?f=-5%20%2B%207q-5q-9q%20%3D)
We add similar terms taking into account that:
- Equal signs are added and the same sign is placed.
- Different signs are subtracted and the major's sign is placed:
![-5 + 2q-9q =\\-5-7q](https://tex.z-dn.net/?f=-5%20%2B%202q-9q%20%3D%5C%5C-5-7q)
Answer:
![-5-7q](https://tex.z-dn.net/?f=-5-7q)
Answer:
the correct answer is
Step-by-step explanation:
hope this helps u!!
A= angle
S= side
This would be AAA, so the answer is C since that answer is not here:)